Konstruksi Metodologi Dakwah dalam Al-Qur’an Berdasarkan Kajian Kitab Tafsir Ibnu Katsir - Zuni Nurrochim; Sri Ningrum; Imam Nur Rahman (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study examines the construction of da'wah methodology in the Qur’an based on Imam Ibn Kathir’s interpretation in Tafsir Al-Qur’an Al-‘Azhim. The research focuses on Qur’anic verses that explain the commands, principles, and methods of da'wah practiced by the prophets and messengers. Using a library research method, this study places Tafsir Ibn Kathir as the primary source, supported by relevant tafsir works and academic literature. The findings show that the Qur’anic da'wah methodology, according to Ibn Kathir, follows a universal and consistent pattern grounded in tawhid, wisdom, good advice, and courteous dialogue. The da'wah of the prophets shares a common objective, namely inviting people to worship Allah alone, obey His commands, and follow the messengers sent to them. The novelty of this study lies in its systematic formulation of Qur’anic da'wah methodology through Ibn Kathir’s classical interpretation, revealing the continuity of da'wah principles across prophetic generations. The study also emphasizes that effective da'wah depends on the suitability of methods to audience conditions and the moral example of the da’i. Therefore, this methodological construction is both normative and practical for contemporary da'wah challenges. It strengthens understanding of prophetic communication ethics in responding to diverse social and religious contexts today. This research contributes to the development of da'wah and tafsir studies and may serve as a conceptual reference for Qur’an-based da'wah practice.